Effectiveness of Rapid Urease Diagnostic Test in Diagnosing Helicobacter Pylori Infection in Patients with Dyspepsia in Gastrointestinal Endoscopy Centre - Hasan Maulahela; Ari Fahrial Syam; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Helicobacter pylori is one of the most important infectious agents in the world. These bacteria infect 50% of the world population. Gastritis due to H. Pylori has been associated with the incidence of peptic ulcer, B cell primary lymphoma in the stomach, and gastric carcinoma. In dyspepsia, eradication of H. Pylori helps symptoms improvement and treatment cost efficiency. This study aimed to evaluate urease test in diagnosing H. Pylori infection in dyspepsia patients. It is expected that we could obtain a scientific evidence which can become the basis of routine use of urease examination in diagnosing H. Pylori  infection.Method: This study used diagnostic study design. This study was performed in adult dyspepsia patients who underwent endoscopy examination in Gastrointestinal Endoscopy Centre Cipto Mangunkusumo General Hospital in January – November 2018. One biopsy sample was intended for rapid urease test using Helicotec which was performed according to the standard procedure and was interpreted 2 hours later. Biopsy for histopathological examination was preserved in formalin solution and sent to Histopathology Department for analysis and identification of H. Pylori bacteria. Results: Prevalence of H. pylori infection based on histopathology examination was 7.2%. From seven positive results in histopathology examination, four samples were Helocitec positive. The sensitivity and specificity of Helicotec was 57.1% and 98.9%. The positive predictive value and negative predictive value were 80% and 96.7%. Conclusion: Rapid urease examination using Helicotec is one of H. pylori diagnostic tools that is good enough to diagnose faster and cheaper. Interpretation of rapid urease test also need to consider clinical condition of patients who are tested.